Vijf jaar aanwinsten hedendaagse kunst 1984-1989. (Arnhem : Gemeentemuseum, 1989)
Akkerman, Philip ; van den Assem, Marjolijn ; Bien, Ania ; Blacker, Kate ; Bloom, Barbara ; Cahn, Miriam ; Dieleman ; Dumas, Marlene ; Elias ; Lee, Eun Young ; Eykelboom, Hans ; Freymuth, Alphons ; Gerritsen, Ad ; Gubbels, Klaas ; Gudmundsson, Sigurdur ; van der Haak, Christie ; Haselhoff, Marianne ; Hendriks, Marten ; Hiethaar, Dorian ; Hoover, Nan ; Horn, Rebecca ; van der Laaken, Ton ; Lafontaine, Marie Jo ; Lucassen ; etc.
Vijf jaar aanwinsten hedendaagse kunst 1984-1989, Gemeentemuseum Arnhem, 22 juli t/m 17 september 1989
boek